UNDERSTANDING THE EFFECTIVENESS OF USING COSPLAY TO RAISE BRAND ATTRACTIVENESS IN INDONESIAâ€™S COMIC INDUSTRY - Agusta, Muhammad Radian; Pritasari, Adita (Journal of Business and Management, 2017)
Abstract. Creative IndustriesÂ refers to a range of economic activities which are concerned with the generation or exploitation of knowledge and information. People suggests that "human creativityÂ is the ultimate economic resourceâ€ and "the industries of the twenty-first century will depend increasingly on the generation of knowledge through creativity and innovationâ€. Indonesiaâ€™s creative industry, specifically comic industry, have been on a more stable rise nowadays. Cosplay become a common phenomenon in Indonesia. Cosplay itself is an act in which people wear costume and accessories to represent specific characters. The practitioners are called cosplayer. This research is intended to understand the effectiveness of using cosplay to raise brand attractiveness. This research uses in-depth interview, to gain information regarding the topic from selected informants of three categories: creator/publisher, cosplayer, and customer. It was found that this method is indeed effective and there are factors supporting it such as: cosplay attracts peopleâ€™s attention/visitor, profile of the cosplayer, the similarity between the cosplayer and the character, and the design of the character itself. This research will hopefully give insight to any industry considering to use this method.Â Keywords:Â  cosplay, comic, comic character, creative industry, brand attractivenessÂ